2015
DOI: 10.1103/physreve.92.023032
|View full text |Cite
|
Sign up to set email alerts
|

Impact of droplets on inclined flowing liquid films

Abstract: The impact of droplets on an inclined falling liquid film is studied experimentally using highspeed imaging. The falling film is created on a flat substrate with controllable thicknesses and flow rates. Droplets with different sizes and speeds are used to study the impact process under various Ohnesorge and Weber numbers, and film Reynolds numbers. A number of phenomena associated with droplet impact are identified and analysed, such as bouncing, partial coalescence, total coalescence, and splashing. The effec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 63 publications
(93 reference statements)
3
27
2
Order By: Relevance
“…This effect of film thickness on the crown direction is also shown clearly in Fig. 12a, and is consistent with previous finding for the impact of droplets on miscible liquid films 23,44 . Figure 12a also shows that the crown propagation speeds for thick films are much slower than that for thin films.…”
Section: Effect Of Film Thicknesssupporting
confidence: 93%
See 2 more Smart Citations
“…This effect of film thickness on the crown direction is also shown clearly in Fig. 12a, and is consistent with previous finding for the impact of droplets on miscible liquid films 23,44 . Figure 12a also shows that the crown propagation speeds for thick films are much slower than that for thin films.…”
Section: Effect Of Film Thicknesssupporting
confidence: 93%
“…This, therefore, demonstrates that the central jet can form on a thin film, without the formation of an impact cavity. There are many scenarios to produce jets due to radially inward flows, such as the formation of a microjet on the surface of a liquid during the impact of a test tube 26 , jet formation accompanying the impact of droplets on superhydrophobic surface 27 and of a large droplet on liquid films due to the formation of a cavity on the upper side of the droplet 23 , the burst of a bubble trapped near a liquid interface 28 , and the collapse of a bubble generated due to cavitation under gravity 29 .…”
Section: Impact Of Water Droplets On Oil Films: Compound Crown and Cementioning
confidence: 99%
See 1 more Smart Citation
“…U is the wall's velocity. Bush 2012; Harris, Liu & Bush 2015) and vibrating/moving liquid surfaces (Sreenivas, De & Arakeri 1999;Couder et al 2005;Terwagne, Vandewalle & Dorbolo 2007;Gilet et al 2008;Che, Deygas & Matar 2015). The isothermal non-coalescence phenomena can be explained as follows.…”
Section: Introductionmentioning
confidence: 99%
“…An asymmetrical crown shape was observed due to the effect of the moving film. Che et al [67] demonstrated the on inclined falling flow asymmetrical crown shape is also formed after droplet impact. Gao and Li [42] further analyzed the early evolvement of droplet impact based on experiments and theoretical model (see Figure 6c).…”
Section: Impact On Flowing Filmsmentioning
confidence: 99%